A novel, rapid in cell RNA amplification technique for the detection of low copy mRNA transcripts. Issue 3 (June 1998) - Uhlmann, V; Rolfs, A; Mix, E; Silva, I; Hully, J; Lu, L; Lohman, K; Howells, D; Picton, S; O'Leary, J J
Abstract : Growing interest now focuses on improvements of in situ polymerase chain reaction (PCR) technology for the detection of DNA and RNA cellular sequences. In this study, reverse transcription PCR in situ hybridisation (RT PCR-ISH) was developed and used to determine gene expression of pyruvate dehydrogenase in a cell model system, using human peripheral blood lymphocytes (PBLs). The success of in cell RNA amplification depends on the type of cell/tissue fixation, cell permeabilisation, and the efficiency of reverse transcription and cDNA amplification. This paper presents new approaches to overcome the critical aspects of fixation, permeabilisation, and reverse transcription when performing in cell RNA amplification. A novel fixative, "Permeafix", possessing fixative and permeabilisation properties, was used for cell fixation procedures. "Permeafix" obviated the need for pre-amplification proteolysis, facilitating entry of PCR reagents to target sequences within the cell. In addition, a simple on step RNA in cell amplification protocol using recombinant Thermus thermophilus (rTth) DNA polymerase, which reverse transcribes mRNA efficiently to cDNA and then catalyses cDNA amplification, was used. The value of a semi-junctional primer system for in cell gene expression studies, without the need to perform DNase digestion, is demonstrated.